2011
DOI: 10.1177/183693911103600206
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Negative Cycle: The Formation of Self-Efficacy Beliefs in the Arts. A Focus on Professional Experience in Pre-Service Teacher Education

Abstract: ACCORDING TO THE NATIONAL Education and the Arts Statement (Ministerial Council on Education, Employment, Training and Youth Affairs, 2007), all children and young people should have a high-quality arts education. To achieve this teachers require a high level of skill and training, and the belief that they are self-efficacious in the teaching of arts education (Andrews, 2004). This points to the role of pre-service teacher education to develop the capability to teach arts education. This study utilises Bandura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 12 publications
(19 reference statements)
2
29
0
6
Order By: Relevance
“…Although completing her final year of university studies, Harley further noted, ‘I haven’t done any creative component as of yet in my degree, no’. This expands upon previous studies in pre-service primary teacher contexts that identified the minimal impact of university coursework on either the visual arts knowledge or low visual arts self-efficacy of students (Garvis et al, 2011; Garvis & Pendergast, 2010). More recently, Smyth and Davis (2016) found that Australian early childhood participants continue to attribute their lack of visual arts knowledge and confidence to minimal visual arts content in their preservice training.…”
Section: Research Findings and Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Although completing her final year of university studies, Harley further noted, ‘I haven’t done any creative component as of yet in my degree, no’. This expands upon previous studies in pre-service primary teacher contexts that identified the minimal impact of university coursework on either the visual arts knowledge or low visual arts self-efficacy of students (Garvis et al, 2011; Garvis & Pendergast, 2010). More recently, Smyth and Davis (2016) found that Australian early childhood participants continue to attribute their lack of visual arts knowledge and confidence to minimal visual arts content in their preservice training.…”
Section: Research Findings and Discussionsupporting
confidence: 74%
“…Acknowledging that beliefs can change over time through the influences of training, experience and work contexts, Mertala (2019) explains that personal beliefs born of early experiences are typically resistant to change and highlights the need for pre-service training contexts to better address pre-service teacher beliefs about subject domains. Eisner’s (1973–1974) null curriculum hypothesis explains that what is not taught by a teacher due to limited subject knowledge and confidence may significantly affect both children’s learning and development and the future pedagogy of educators; producing a negative cycle of influence (Garvis et al, 2011). Despite the passing of almost 30 years since Eisner’s (1973–1974) warnings about the myths of visual arts pedagogy and the risk of a null curriculum, scholars continue to identify that the visual arts beliefs and practices of educators remain entrenched in out-dated developmental, and non-interventionist pedagogical approaches, rather than transitioning to the socio-cultural and constructivist learning theories that guide contemporary practice (Hong et al, 2017; Leung, 2020; Probine, 2017; Terreni, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Trainees can observe another trainee's positive or negative experiences and see how they handle different situations or lessons. It can also directly influence their teacher efficacy by creating distinct experiences through communication and discussion with other pre-service teachers (Bautista, 2011;Deehan, Danaia, & McKinnon, 2017;Garvis, Twigg, & Pendergast, 2011;Hastings, 2012;Hawkey, 1995;Johnson, 2010;LoCasale-Crouch, Davis, Wiens, & Pianta, 2012). Bandura (1997) suggests that another teacher or pre-service teacher's model may affect the observer pre-service teacher's efficacy.…”
Section: Vicarious Experiencementioning
confidence: 99%
“…2.3. Work-related traits in preventing teacher burnout Concerning work-related traits, we consider the teaching style and the professional experience to be the most relevant for the present study because they have been mentioned in the literature as essential in profiling teachers [56][57][58][59].…”
Section: Individual Traits In Preventing Teacher Burnoutmentioning
confidence: 99%